Evaluation of civil servant teacher's restructuring and equalizing policy at vocational high school - Ratih Setianingrum; Guntur Guntur (Graduate School, Universitas Negeri Yogyakarta, 2020)
This study aims to evaluate (1) the implementation and (2) the result of the implementation of civil servant teacher’s restructuring and equalizing policy at vocational high schools in Yogyakarta City. This research was a policy evaluation using the discrepancy evaluation model by identifying the gap between performance and standard. The data was collected through interviews and documentation from several informants, including the Office of Secondary Education staff, vice principals of curriculum, and some civil servant teachers. The instrument validity was tested validated by expert's judgment while the data validity was measured by triangulation. The data were analyzed using the descriptive statistical analysis for analyzing the quantitative data and continuous interactive analysis for analyzing the qualitative data. The research results are as follows. (1) The implementation of civil servant teacher’s restructuring and equalizing policy at vocational high schools in Yogyakarta City had been implemented properly in accordance with the implementation standards. (2) The implementation of civil servant teachers' restructuring and equalizing policy successfully rearranged 15 civil servant teachers and reduced teacher shortages by 4%. Nonetheless, the number of teacher shortages in certain subjects was still quite large, especially in productive subjects. This policy implementation's positive impacts are (a) teachers are motivated to increase their career paths; (b) teachers get new teaching experience and relationships. Meanwhile, the negative impact is that the teachers are having difficulty in managing teaching time, which causes them to not focus on teaching.